The relationship between brand attractiveness and the intent to apply for a job: A millennials' perspective. Issue 2 (8th July 2019) - Santiago, Joanna
Abstract : Purpose: The purpose of this paper is to understand the relation between the dimensions of employer brand (EB) attractiveness and the intention to submit a job application to the organisation. An increase of competitiveness in the business world has resulted in an increased effort by organisations to improve the processes of recruitment and retention of talented professionals, as the human capital of organisations is extremely important for their growth and sustainability. Regardless of an organisation's size, the difficulties faced in recruiting and retaining highly qualified human capital are tangible. In this sense, the research problem identifies EB as being a strategic element for attracting future employees to work for an organisation. Design/methodology/approach: This study used both quantitative (a questionnaire survey) and qualitative (in-depth interviews) data to investigate the perceptions of future and current employees. Findings: Evidence from 281 respondents (of which almost 60 per cent belong to the millennial generation) who participated in the quantitative study supports the multi-dimensionality of EB attractiveness, highlighting the importance of economic factors, such as an above-average salary or opportunities for promotion, which are seen to be less important to millennials when considering future job prospects. Interestingly, the results of the qualitative research for current employees show slightly different concerns, in that career progression appears to be crucial. Originality/value: The study findings not only offer a basis for research on the dimensions of employer attractiveness, but also, they serve as a managerial guide towards enhancing companies' ability to attract, retain and motivate talented individuals.